THE POWER OF OPEN-ENDED QUESTION AND ITS CRUCIAL ROLE IN DISCOVERING UNANTICIPATED ANSWERS, GATHERING ADDITIONAL DETAILS AND IMPORTANT INSIGHTS - Nilufar Mirzaholova Komildjanovna (Web of Journals Publishing, 2024)
This study explores the role of open-ended questions in enhancing communication during interviews. The research highlights how these questions encourage deeper responses, foster engagement, and reveal underlying thoughts and feelings of participants. A mixed-methods approach was employed, utilizing surveys and interviews with interviewers and candidates across various fields. The results indicate that open-ended questions significantly improve the quality of responses, leading to more insightful discussions. Additionally, the findings suggest practical strategies for incorporating open-ended questions into interview practices to facilitate better communication and understanding. This research contributes to the field of communication studies by demonstrating the effectiveness of open-ended questions in various contexts.
Keywords: open-ended questions in education, questioning techniques in communication, role of open-ended questions, conversational psychology, closed-ended responses, social nature of learning.